Taxonomic notes on the shrublet species of Acanthopsis (Acanthaceae, tribe Acantheae), with two new species from South Africa - Steyn, Hester Maria; van Wyk, Abraham E (Phytotaxa, 2016)
The taxonomy of Acanthopsis is poorly understood, resulting in great difficulties in distinguishing and identifying infrageneric taxa. In this contribution a taxonomic account of the shrublet members of Acanthopsis is provided. Four species are recognized, two of which are newly described, namely A. dregeana and A. erosa (both confined to the Northern Cape Province, South Africa). Acanthopsis trispina, hitherto only known from the orginal collection, is considered a synonym of A. horrida. Acanthopsis spathularis has been recollected after more than 180 years and its status as a distinct species is confirmed. The names A. spathularis and A. horrida are lectotypified here. An identification key to the species of the shrublet group in Acanthopsis is provided.